(untitled) (Journal of Forensic Medicine & Toxicology, 2011)
A young executive was found dead in the early morning on the road near a railway track. He was a known alcoholic. The previous night he had gone to a local liquor shop, located near a railway track, selling cheap, locally made liquor. He was assaulted by some unidentified person, with a sharp weapon, while he was returning to his home after consuming alcohol. He was found dead the next morning.